Bias‐Free Solar Water Splitting by Tetragonal Zircon BiVO4 Nanocrystal Photocathode and Monoclinic Scheelite BiVO4 Nanoporous Photoanode. (25th November 2020) - Liang, Xizhuang; Wang, Peng; Tong, Fengxia; Liu, Xiaolei; Wang, Cong; Wang, Minrui; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Dai, Ying; Huang, Baibiao
Abstract: p‐type tetragonal zircon BiVO4 nanocrystal photocathodes (P‐BVO) and n‐type monoclinic scheelite BiVO4 nanoporous photoanodes (N‐BVO) are prepared by a hydrothermal method and an electrochemical synthesis method, respectively. Pt nanoparticles and cobalt‐phosphate (Co‐Pi) as co‐catalysts are loaded by an electrodeposition way to improve the photoelectrochemical (PEC) performance of BiVO4 (BVO) electrodes. After modification, a monochromatic incident photon‐to‐current conversion efficiency (IPCE) of P‐BVO/Pt at 360 nm is improved by 2.2 times, and the highest IPCE of N‐BVO/Co‐Pi at 440 nm is increased by 1.7 times. The calculated electron‐hole separation yield and the charge carrier injection yield of N‐BVO/Co‐Pi at 1.23 VRHE are further improved to 80% and 86%, respectively. The surface modification also results in the latest ≈0.2% half‐cell solar‐to‐hydrogen energy conversion efficiency (HC‐STH) for a P‐BVO/Pt photocathode and a higher ≈1.16% half‐cell applied bias photon‐to‐current conversion efficiency (ABPE) for an N‐BVO/Co‐Pi photoanode. Furthermore, the prepared photoelectrodes are proved to have excellent stability for water splitting. Above all, a tandem‐type PEC cell containing the newly developed P‐BVO/Pt photocathode and an N‐BVO/Co‐Pi photoanode is built for the first time, which evolves H2 and O2 at a stoichiometric ratio of 2:1 with a bias‐free STH of 0.14%. Abstract : The tetragonal zircon BiVO4 /Pt and monoclinic scheelite BiVO4 /Co‐Pi are designed as efficient photocathode and photoanode, respectively. The high performance can be attributed to the morphology control and the co‐catalysts modification to improve the carrier separation efficiency. A tandem photoelectrochemical cell composed of the above photoelectrodes successfully achieves bias‐free solar water splitting with a solar‐to‐hydrogen energy conversion efficiency of 0.14%.